PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP EFEKTIVITAS SEKOLAH PADA SEKOLAH MENENGAH KEJURUAN NEGERI DI PROVINSI JAMBI - Istikomah, Istikomah (UIN Imam Bonjol Padang, 2020)
Principal's leadership is one of the supports success of a school to be an effective school. Being an effective school there needs to be a strong headmaster's leadership because the meaning of leadership is one's attitude to be able to influence others in order to work according to their responsibilities and achieve desired goals. This research is quantitative research with a survey method. From the results of this study, it was found that the principal's leadership style significantly influenced the effectiveness of schools in the State Vocational High School in Jambi Province. Based on the results of the analysis, the obtained value of thitung (8,54) > ttabel (1,969),Â H0 is rejected and H1 is accepted. This means that the high leadership style of the principal has a significant influence on school effectiveness. This means that the extent effectiveness of application the principal's leadership style will result, increase in school effectiveness. The research implications of these findings explain that better the principal's leadership style, more influential school's effectiveness will be.